2023
DOI: 10.1038/s41467-023-36393-4
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and optimization of a broadly-neutralizing human monoclonal antibody against long-chain α-neurotoxins from snakes

Abstract: Snakebite envenoming continues to claim many lives across the globe, necessitating the development of improved therapies. To this end, broadly-neutralizing human monoclonal antibodies may possess advantages over current plasma-derived antivenoms by offering superior safety and high neutralization capacity. Here, we report the establishment of a pipeline based on phage display technology for the discovery and optimization of high affinity broadly-neutralizing human monoclonal antibodies. This approach yielded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 54 publications
3
53
0
Order By: Relevance
“…The scFv genes from the third selection round were amplified using PCR and subcloned using NcoI and NotI restriction endonuclease sites into the pSANG10-3F vector for expression of soluble scFvs transformed into E. coli BL21(DE3) cells (New England Biolabs), as previously descrived [6,10]. The pSANG10-3F vector contains a FLAG-tag and a 6xHis tag in phase with the scFv.…”
Section: Subcloningmentioning
confidence: 99%
See 1 more Smart Citation
“…The scFv genes from the third selection round were amplified using PCR and subcloned using NcoI and NotI restriction endonuclease sites into the pSANG10-3F vector for expression of soluble scFvs transformed into E. coli BL21(DE3) cells (New England Biolabs), as previously descrived [6,10]. The pSANG10-3F vector contains a FLAG-tag and a 6xHis tag in phase with the scFv.…”
Section: Subcloningmentioning
confidence: 99%
“…Recently, it has been demonstrated that broadly-neutralizing mAbs (bnAbs) targeting animal toxins can be developed using cross-panning strategies in phage display selection campaigns 5,6 , by semi-rational design and directed evolution 7 , and by high-throughput screening of B-cells from immunized individuals 8 . Here, we demonstrate the utility of a fourth strategy that uses consensus toxins, which are artificial toxins based on the average sequence of related toxins 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The Sc-α-NTx 'SHORT NEUROTOXIN alpha (NP)' (listed with the recommended name 'short neurotoxin 1' (sNTx1) on the UniProt database; P01426) isolated from Naja pallida venom was purchased from Latoxan (L8101, Valence, France), and the Lc-α-NTx, 'αbungarotoxin' (α-BgTx), isolated from Bungarus multicinctus venom was purchased from Biotium (0010-1, Fremont, CA, USA). Lymnaea stagnalis (Ls-AchBP) was prepared as previously described [17], as were the fully human monoclonal antibodies (mAbs) 2551_01_A12, 2554_01_D11 and 367_01_H01 in IgG1 format [21]. Samples of the various small molecule drugs used for screening were obtained by request from the Open Chemical Repository of the Developmental Therapeutics Program (https://dtp.cancer.gov) (Division of Cancer Treatment and Diagnosis, National Cancer Institute, Rockville, MD, USA), except for nicotine (see section 2.1.2) and varespladib (SML1100, Sigma-Aldrich, Gillingham, UK).…”
Section: Nachr Agonists and Antagonistsmentioning
confidence: 99%
“…To explore the utility of our assay as a functional screen to detect novel toxin-inhibitory molecules, we selected representatives of these different therapeutic formats (antivenoms, small molecule drugs, nAChR-mimicking proteins, and monoclonal antibodies) and assessed their ability to inhibit the nAChR antagonism stimulated by representative neurotoxic snake venoms (from N. haje and D. polylepis) and α-NTxs (α-BgTx and sNTx1). In line with the WHO guidelines for preclinical testing of antivenoms [13] and many other in vitro and in vivo approaches to assess venom inhibition [17,21,28,52], we performed these experiments with an initial pre-incubation step, where inhibitor and venom/toxin were co-incubated at 37 °C for 30 min before assaying, to give the inhibitor maximal opportunity to exhibit neutralisation (Fig. 5).…”
Section: Neurotoxic Snake Venoms Block the Ach Response Of Te671 Cellsmentioning
confidence: 99%
See 1 more Smart Citation